PENGARUH TATA KELOLA PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN EMISI KARBON DI INDONESIA - Amrie Firmansyah; Pramuji Handra Jadi; Wahyudi Febrian; Deddy Sismanyudi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
The company has a significant contribution to industrialization, which results in global warming and climate change in the world. This condition can threaten the future of the world, including in Indonesia. This study aims to examine the effect of corporate governance on the disclosure of carbon emissions in Indonesia. This study uses secondary data sourced from financial statements available at www.idnfinancials.com. The sample used in this study was a manufacturing company from 2016 to 2019. By using purposive sampling, the sample obtained in the study is 260 observations. The research data were analyzed using multiple linear regression for panel data. This study concludes that the implementation of good governance and firm size are positively associated with emission carbon disclosure. The implementation of good corporate governance can increase the transparency of information provided to the public voluntarily, including information on carbon emissions produced by companies. Besides, the large companies tend to be transparent in their carbon emissions disclosure to the public. This research indicates that the government needs to regulate policies related to managing carbon emissions produced by companies to encourage companies to implement sustainability issues. In addition, the Financial Services Authority (OJK) needs to carry out monitoring related to the implementation of corporate governance implemented by companies listed on the Indonesia Stock Exchange.